(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The year 2019- 2020 has given rise to a menace in the form of Corona Virus Disease, which within no time has turned into a pandemic, affecting every corner of the world. It has disarranged the day-to-day lifestyle of the society, economy, employment, trade, hunger, etc. Dentistry is also one of these, affected by the pandemic, and has caused heavy financial loss for the dental personnel, along with delay/halt in the dental treatment to a massive population in need. When eradicating the disease has become a question, it is better to live with the disease and restrain the risks of transmission in the dental operatory by following few crucial and mandatory steps like proper hand hygiene, maintaining social distancing, creating awareness, fumigating the operating rooms and surfaces etc. This review article thus elaborates the expedients a dental surgeon should follow to combat the risks of transmission of this fierce disease during dental interventions.